Employee-friendly practices and innovation - Saeyoung Chang; Hoje Jo; Jo-Ellen Pozner (The Journal of Entrepreneurial Finance (JEF), 2022)
We examine the inter-relationships among employee-friendly policies (EFP), innovation through R&D investment, and firm value. We hypothesize that firms with higher levels of innovation and entrepreneurial spirit are more likely to utilize EFP. Furthermore, we speculate that the value-EFP association is more pronounced in firms with high R&D intensity. Consistent with these assertions, we find that EFP is significantly and positively related to R&D investment and the number of patents. EFP is also associated with increased firm value at high levels of R&D investment and high numbers of patents. Furthermore, we find that firms investing more in R&D are more likely to treat their workers favorably and that markets react positively when such firms are recognized for their favorable treatment of employees. Our analysis, based on a large sample of U.S.-based firms and two different measures of employee-friendly policies, supports the assertion that EFP based on sustainable innovation and entrepreneurial mindsets contributes to value creation
Keywords: G30; G39; O32; 650; Employee-friendly practices; Human capital; R&D investment; Sustainable innovation; Entrepreneurial spirit; Value creation theory